Megemlékezés dr. Fónyad Dezsőről az SDG alapításának 100. évfordulója alkalmából - BÁRÁNY, Zoltán (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Commemorating Dr Dezső Fónyad on the Occasion of the 100th Anniversary of the Foundation of SDG. Dr Dezső Fónyad (1906–1965) was a Reformed pastor in Monor, publicist, and one of the spiritual leaders of the Soli Deo Gloria Reformed student movement. Between the two world wars, the Soli Deo Gloria student movement (SDG for short) was a major force in the field of faith, church identity, and national edu-cation among Reformed university and then secondary school students. In the 1930s, the nationally known youth pastor’s popularity and recognition grew dy-namically, but after World War II, amid the internal political turmoil in the country, he was prosecuted on false charges at the People’s Court. During World War II, he and his colleagues in the SDG rescued Jews, and these same colleagues testified for him at his trial by the People’s Court.